Socio-Economic Drivers of Benefits from Agri-Environmental Measures among Rural Farming Households in Akinyele Local Government Area of Oyo State, Nigeria - Bobadoye, A. O.; Aluko, O. J.; Oyewole, O. O.; Olusina, O. P. (NIU Journal of Social Sciences, 2025)
The study investigated the socio-economic characteristics of rural farming households, the types of Agri-Environmental Measures (AEMs) adopted, and the determinants of benefits derived from participation in Akinyele Local Government Area of Oyo State, Nigeria. A total of 240 farmers were surveyed using a multi-stage sampling procedure. The results showed that 36.7% of respondents were aged 41–50 years, 67.5% were male, and 53.4% had secondary or tertiary education. Most farmers (80.8%) had over 10 years of farming experience, while 64.2% belonged to cooperatives and 70% had extension contact. Farmers mainly adopted organic manure (71.7%), soil conservation (67.5%), controlled chemical use (65%), agroforestry (61.7%), and climate-smart practices (57.5%).Binary logistic regression showed that farm size (β = 0.311, p = 0.003 ) , cooperative membership (β = 0.842, p = 0.000), extension contact (β = 1.124, p = 0.000), income (β = 0.514, p = 0.005), and farming experience (β = 0.042, p = 0.020 ) significantly increased the likelihood of benefiting from AEMs. Age had a mild negative effect (β = –0.028, p = 0.048 ) , while education and household size were not significant. The study concluded that socio-economic readiness, institutional support, and access to information strongly shaped the probability of deriving benefits from AEM participation. Strengthening extension services and farmer cooperatives was essential for enhancing AEM effectiveness. Keywords: Benefit, agricultural, environmental measures, participation and farming households.